2021
DOI: 10.3389/fimmu.2021.724200
|View full text |Cite
|
Sign up to set email alerts
|

SNAIL1: Linking Tumor Metastasis to Immune Evasion

Abstract: The transcription factor Snail1, a key inducer of epithelial-mesenchymal transition (EMT), plays a critical role in tumor metastasis. Its stability is strictly controlled by multiple intracellular signal transduction pathways and the ubiquitin-proteasome system (UPS). Increasing evidence indicates that methylation and acetylation of Snail1 also affects tumor metastasis. More importantly, Snail1 is involved in tumor immunosuppression by inducing chemokines and immunosuppressive cells into the tumor microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 169 publications
(179 reference statements)
1
19
0
Order By: Relevance
“…Increasing evidence suggests that the malignant behaviors and treatment resistance of cancers are heavily governed by the crosstalk between the TME and tumor cells 28 . Chemokines are crucial in modulating the activity and tolerance status of tumors, as well as the abundance and cellular differentiation of TILs involved in pro-and anti-tumorigenic immune activities [29][30][31][32] . Previous studies found high CCL5 expression in PBRM1 MUT ccRCC patients that exhibited poor clinical outcomes and increased mast cell infiltration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that the malignant behaviors and treatment resistance of cancers are heavily governed by the crosstalk between the TME and tumor cells 28 . Chemokines are crucial in modulating the activity and tolerance status of tumors, as well as the abundance and cellular differentiation of TILs involved in pro-and anti-tumorigenic immune activities [29][30][31][32] . Previous studies found high CCL5 expression in PBRM1 MUT ccRCC patients that exhibited poor clinical outcomes and increased mast cell infiltration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…SNAI1 is a zinc finger transcription factor and functions as a driver of cancer progression [97]. Numerous studies have shown that Snail1 is a crucial inducer of EMT and plays a vital role in tumor metastasis [98].…”
Section: Snai1mentioning
confidence: 99%
“…Above all, Snail is modulated by various signal pathways at the transcriptional and post-translational levels [ 3 , 4 ]. Snail is degraded by the E3 ligase-dependent ubiquitin proteasome system [ 5 ]. Zhou et al previously identified that β-TrCP1 ubiquitinates Snail through its phosphorylation by GSK-3β [ 6 ].…”
Section: Introductionmentioning
confidence: 99%